Stimulus-responsive adsorbent materials for CO2 capture and separation. Issue 21 (19th May 2020) - Wang, Maohuai; Zhou, Sainan; Cao, Shoufu; Wang, Zhaojie; Liu, Siyuan; Wei, Shuxian; Chen, Yong; Lu, Xiaoqing
Abstract : Stimulus-responsive adsorbent materials exhibit tunable CO2 capture and separation performance in response to pressure, temperature, light, electric field, magnetic field, guest molecules, pH, and redox. Abstract : CO2 capture and separation by using adsorbent materials have exhibited great potential for application in strategies that alleviate environmental degradation. Stimulus-responsive adsorbent materials, a kind of advanced functional materials, have recently attracted tremendous interest. These materials can recognize external stimuli and exhibit tunable physical or chemical properties, thus controlling CO2 adsorption and separation behaviors. This review highlights the recent developments of stimulus-responsive adsorbent materials that can modulate CO2 capture and separation properties in response to some specific stimuli, including pressure, temperature, light, electric field, magnetic field, guest molecules, and other newly emerging stimuli. To understand stimulus-responsive behaviors in depth, the response mechanisms are summarized and elucidated. This review also proposes future directions in the development of stimulus-responsive materials for CO2 capture and separation.